OPTIMALISASI LITERASI KEAMANAN DIGITAL MELALUI EDUKASI PERLINDUNGAN KONSUMEN UNTUK MENCEGAH PENIPUAN ONLINE - Hirawati Lubis; Syarkawi Syarkawi; Yulianti Rusdiana; Putri Maharani Fauziah; Syamsul Bahtiar; Aji Santoso; Rinanda Syahputri; Ana Farkhi Mufarohah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The rapid growth of digital technology has increased public exposure to cyber fraud and digital consumer risks, while digital literacy among community members remains limited. This community service program aimed to enhance public awareness and knowledge of cyber fraud prevention and digital consumer protection through simulation-based education. The program was implemented at RPTRA Serdang Baru using lectures, interactive discussions, practical simulations, educational booklets, digital learning media, and post-test evaluation. The results indicated improved participant understanding of common cyber fraud schemes, personal data protection, and appropriate responses to digital fraud incidents. The program also strengthened participants' confidence in conducting safe digital transactions. These findings demonstrate that interactive educational approaches effectively improve community digital literacy and support safer participation in the digital environment.Keywords: Digital literacy; Cyber fraud prevention; Consumer protection; Simulation-based education